Influences of thermal radiation and sar from 900/1800 mhz handheld mobile phone towards modelled human head - Kho, Franky Wee Tat (Universiti Malaysia Sarawak (UNIMAS), 2009)
Mobile communication is currently the fastest growing communication system in the telecommunication industry. Mobile communication is the wireless communication where signal is transferred by electromagnetic radiation such as radio frequency and microwave. Since electromagnetic radiation consist of harmful ionizing radiation and harmless non-ionizing radiation, the concern about the harmful effects upon human’s tissues exposed to the steady electromagnetic energy is growing. This project is going to analyze the effect of the thermal radiation and specific absorption value on two types of mobile phones with different frequencies. Clay and water molecule are used as the phantom composition of the modeled head for experimental analysis. Mobile phone with internal and external antenna are used in comparison for higher radiation effects. Thermal imaging technique is used to monitor and capture the temperature distribution during the experimental analysis by using an infrared camera. From the result of experimental analysis, the external antenna mobile phone with GSM 900MHz will cause highest radiation effect while built in antenna mobile phone with GSM 1800MHz will cause the lowest radiation effect. However, the mobile radiations of these both types of mobile phone do not cause adverse health to human in short term. Although the radiation effects of the mobile phone is minor for short term effect, the long term effects of the radiation need to be considered. In conclusion, mobile phone user should be aware and concern on the mobile phone radiation due to it long term effect.